Combined physiological and transcriptome analysis revealed the response mechanism of Pogostemon cablin roots to p-hydroxybenzoic acid - Yan, Wuping; Cao, Shijia; Liu, Xiaofeng; Yao, Guanglong; Yu, Jing; Zhang, Junfeng; Bian, Tengfei; Yu, Wengang; Wu, Yougen (Frontiers in Plant Science, 2022)
Pogostemon cablin (patchouli) cultivation suffers from serious continuous cropping obstacles. The main causes of continuous cropping obstacle of patchouli were the imbalance of rhizosphere soil microbial community structure and accumulation of allelochemicals. P-hydroxybenzoic acid (p-HBA) is the main allelopathic autotoxic substance of patchouli and has obvious autotoxic effect on the growth of patchouli. However, the molecular mechanism of patchouli response to p-HBA remains unclear. In this study, RNA-sequencing (RNA-Seq) technology combined with physiological analysis was used to supervise the dynamic changes of transcriptome and physiology of patchouli seedlings at 0, 6, 12, 24, 48 and 96 h after p-HBA treatment. The results showed that p-HBA stress inhibited root biomass accumulation, induced excessive accumulation of hydrogen peroxide and lipid peroxidation, and activated most antioxidant enzymes. Compared with the control, osmotic adjustment substance content was always at a high level. The functional annotations of DEGs indicated that p-HBA negatively affects biological regulation. DEGs are mainly enriched in plant-pathogen interaction, MAPK signaling pathway-plant, plant hormone signal transduction pathways. These factors directly led to poor root growth of patchouli seedlings and eventually led to plant death. This study provides effective information for revealing the response mechanism of patchouli roots to autotoxicity, and provides a theoretical basis for solving continuous cropping obstacles of patchouli.